2022
DOI: 10.1186/s12934-022-01749-w
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal approaches for the improvement of the cellular folding of a recombinant iron regulatory protein in E. coli

Abstract: Background During the recombinant protein expression, most heterologous proteins expressed in E. coli cell factories are generated as insoluble and inactive aggregates, which prohibit E. coli from being employed as an expression host despite its numerous advantages and ease of use. The yeast mitochondrial aconitase protein, which has a tendency to aggregate when expressed in E. coli cells in the absence of heterologous chaperones GroEL/ES was utilised as a model to investigate how the modulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Low culture temperature for recombinant protein expression in E. coli is a well-established strategy to suppress IB formation ( 13 ). At low temperatures, protein solubility is enhanced, and protein aggregation is reduced ( 14 ). Therefore, based on these findings, it is evident that temperature control from 37°C to 30°C effectively suppresses IB formation and enhances the endogenous CO 2 recycling capacity of the CBB strain.…”
Section: Resultsmentioning
confidence: 99%
“…Low culture temperature for recombinant protein expression in E. coli is a well-established strategy to suppress IB formation ( 13 ). At low temperatures, protein solubility is enhanced, and protein aggregation is reduced ( 14 ). Therefore, based on these findings, it is evident that temperature control from 37°C to 30°C effectively suppresses IB formation and enhances the endogenous CO 2 recycling capacity of the CBB strain.…”
Section: Resultsmentioning
confidence: 99%
“…Images of the stained gel were captured using a Bio-Rad Molecular Imager® Gel Doc XR + Imaging Unit. The relative quantification of band intensity was estimated using Image Lab® software in the Bio-Rad Molecular Imager Gel Doc XR + unit by densitometric analysis [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Raziyeh Malekian et al used molecular chaperones to achieve soluble expression of GM-CSF protein in E. coli [21]; Safar Farajnia et al found that molecular chaperones have signi cant advantages in improving soluble expression of Fab antibody in E. coli [22]; Shuaiying Peng et al studied found that co-expression of PFA with molecular chaperone proteins signi cantly increased the soluble expression of PFA [23]. So we continued to combine molecular chaperones to alter the soluble expression of s-oph proteins [24].…”
Section: Expression Of the S-oph Gene In E Colimentioning
confidence: 99%